Resistance to Ideal Body Standards: Self-Presentation and Self-Image of Plus-Size Female Influencers on Instagram - Anggie Nur Fitrianti; Christania Pingkan Putrinita; Kamaratih Purnama Kusuma; Meyta Roida Rebecka Hutapea (Yayasan Ilomata, 2026)
This study aims to understand how plus-size female influencers in Indonesia interpret their self-image and self-presentation on Instagram as the social media platform, particularly within the context of dominant societal standards of the ideal female body. By using a qualitative approach and digital ethnographic method, data were collected through in-depth interviews and content observation of three informants’ Instagram accounts. The findings reveal three key aspects: (1) the meaning of self image for plus-size women; (2) the influence of audience on reflecting self-presentation and self-image; and (3) strategies of self-presentation on social media. The informants demonstrated an authentic of themselves, while creating a digital space that promotes inclusivity and affirmation. Instagram emerged not only as a medium of expression, since it also performed as a social stage where women actively negotiate their identities. This study adds valuable insights to digital communication fields, particularly in understanding the construction of self-representation and body image in the era of digital and social media.